(untitled) (Sir Salimullah Medical College Journal, 2022)
Background: Hospital based data of diseases profile are reflection of community at large. Being in COVID pandemic era, knowledge of disease pattern and outcome in children is crucial for proper resource allocation and health care planning. Performance evaluation of each hospital has become central to the concept of quality improvement. Objective: to evaluate disease pattern and outcome of a non COVID hospital in COVID era. Methodology: This retrospective descriptive study was conducted in pediatric unit (1 months to 14 year) of Sir Salimullah Medical College Mitford Hospital from January, 2021 to December, 2021. Medical records were reviewed and analyzed for age, gender, disease, duration of hospital stay, bed occupancy rate and outcome. Results: Total 4346 patients were admitted of which male is 68%. Most admission was in between 1 month to 12 months of age which is 48.5%. Bronchopneumonia, Dengue and Bronchiolitis became the top 3 cause of admission. 70% patients stayed less than 7 days. 2% patients were referred of which maximum were later diagnosed as COVID-19 patients. Bed Occupancy rate was 138% and Bed Turn Over rate was 72.4 patients/bed/year. Mortality rate was 1.6%. Conclusion: To achieve SDG 3 goal by 2030, assessment of hospital performance as well as disease profile of each hospital is needed for proper resource allocation and community improvement. Sir Salimullah Med Coll J 2022; 30: 168-174